Konsep Membangun Dzurriyyatan Thoyyibatan dalam Menghadapi Bonus Demografi dalam Perspektif Al-Qur’an - Sembiring, Ghita Kinanti Pratiwi (ANWARUL, 2023)
This research is entitled The Concept of Building Dzurriyyatan Thayyibatan in Facing Demographic Bonuses in the Perspective of the Koran. The problems studied are first: what is meant by Demographic Bonus, second: how does the Qur'an deal with Demographic Bonus, third: how does the concept of building dzurriyyatan thayyibatan in the Qur'an deal with demographic bonus. This study uses a library research approach with the maudhu'i interpretation method. Sources of data taken in this study were books, journals related to the research title, also using commentary books. The results of this study are that in dealing with the demographic bonus, several aspects that support the success of the demographic bonus are then juxtaposed with the Qur'an. Then in forming and producing dzurriyyatan thayyibatan it is necessary to have an educational method that is in accordance with the Koran. Like parents who always pray for kindness to their children, as well as other educational methods.